Studi Tentang Informasi Akuntansi Dalam Manajemen Laba Menggunakan Model Jones Dimodifikasi Sebagai Dasar Keputusan Investasi - Wulandari, Tiara (Pusat Riset dan Inovasi Nasional, 2025)
This study empirically examines the effect of earnings management on stock price as a basis for investment decisions in agricutural sector companies listed on the Indonesia Stock Exchange (IDX) during 2016-2023. Earnings management is measured using the Modified Jones Model, and stock prices are based on year-end closing prices. A quantitative approach with secondary data and purposive sampling was applied to 15 companies (120 observations). The results show that earnings management has a significant effect on stock prices. These findings suggest that such practices influence investor perceptions and investment decisions, highlighting the importance of transparency and accounting information quality in maintaining market efficiency.